Alternative medicine: Intent of analysis - Peña, Adolfo (2007)
Alternative medicine is considered a set of therapeutic and diagnostic disciplines that exist outside the conventional health system. Current use of this 'class' of medicine is amply extended in both developed and undeveloped world. One of the causes of increasing use of alternative medicine is recent professional validation. Many general divulgation texts claim and justify its use based on academic information without scientific quality. In this essay we will analyze the available scientific evidence as well as logical and philosophical bases of this so called medicine.